Proceedings of the 3rd International Symposium on Big Data and Cloud Computing Challenges (ISBCC - 16') - Vijayakumar, V.; Neelanarayanan, V. (Smart Innovation, Systems and Technologies,, 2016)
This proceedings volume contains selected papers that were presented in the 3rd International Symposium on Big data and Cloud Computing Challenges, 2016 held at VIT University, India on March 10 and 11. New research issues, challenges and opportunities shaping the future agenda in the field of Big Data and Cloud Computing are identified and presented throughout the book, which is intended for researchers, scholars, students, software developers and practitioners working at the forefront in their field. This book acts as a platform for exchanging ideas, setting questions for discussion, and sharing the experience in Big Data and Cloud Computing domain.